Investment and Growth in the Arab World : A Scoping Note. (Policy Papers; Policy Paper ;, 2016)
Enhancing public and private investment, but also ensuring that this translates into higher growth and employment, have long been key policy challenges in Arab countries. Reflecting an improvement in policies and global conditions, investment rates in Arab countries have increased over the past couple of decades. In spite of this-and notwithstanding significant differences across the region-investment has on average been somewhat weaker than in peer countries and less effective at generating growth. Private investment, particularly foreign direct investment (FDI), has underperformed significantly. And while public capital spending has benefited from high oil prices in resource-rich countries, it has continued to lag in oil importers...